2012
DOI: 10.6001/actamedica.v19i2.2311
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of esophageal varices after endoscopic band ligation: single centre experience

Abstract: Background and objective. Endoscopic band ligation is the main endoscopic treatment for esophageal varices, but the main problem after endoscopic treatment is variceal recurrence. The aim of this study was to evaluate and determine the esophageal varices recurrence rate and the time interval after endoscopic band ligation and to investigate possible risk factors affecting recurrence. Material and methods. The retrospective analysis of endoscopic band ligation procedures, performed in Vilnius University Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Recurrence of bleeding was much more in intra-hepatic cases (91.7%) than extra-hepatic cases (8.3%). 15 In our study, recurrence of bleeding occurred in 100% intra-hepatic cases and 50% prehepatic cases. Masalaite et al 15 also showed that early re-bleeding was more in intra-hepatic cases (82.1%) & less in pre-hepatic (17.9%) cases.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recurrence of bleeding was much more in intra-hepatic cases (91.7%) than extra-hepatic cases (8.3%). 15 In our study, recurrence of bleeding occurred in 100% intra-hepatic cases and 50% prehepatic cases. Masalaite et al 15 also showed that early re-bleeding was more in intra-hepatic cases (82.1%) & less in pre-hepatic (17.9%) cases.…”
Section: Discussionmentioning
confidence: 91%
“…Once varices have developed, they increases in size and eventually cause variceal bleeding. 15 This is an emergency with high rates of morbidity & mortality. 12 EVL is the gold standard for the treatment of acute bleeding of esophageal varices.…”
Section: Discussionmentioning
confidence: 99%